Physical Inactivity and Food Insecurity Are Associated with Social Capital: A Large-Scale Population-Based Study in Tehran - Amin Nakhostin-Ansari; Paria Akbari; Maryam Selk-Ghaffari; Amir Hossein Memari; Mohamad-Reza Vaez-Mahdavi; Mohsen Asadi-Lari (The Scientific World Journal)
Background. There are limited studies on food security, physical activity, and social capital in the Iranian population. This study aimed to evaluate the social capital’s associations with physical inactivity and food insecurity in a large-scale study in Iran, Urban HEART-2. Methods. This cross-sectional study was conducted in 22 districts of Tehran, the capital of Iran. Residents of Tehran who were 15 years or older were selected by a multi-stage, stratified, and random sampling method. Food insecurity and physical activity were evaluated using Household Food Security Scale and Global Physical Activity Questionnaire, respectively, and their associations with social capital were evaluated. Results. A total of 5030 individuals were included in this study, with 3139 (62.4%) males. The mean age of participants was 44.08 years (SD = 16.33, range = 15–90). Participation in social events (OR = 0.893, 95% CI = 0.819–0.974, P = 0.011), social network (OR = 0.849, 95% CI = 0.786, P < 0.001), and voluntary activities (OR = 0.865, 95% CI = 0.812–0.921, P < 0.001) were all negatively associated with food insecurity. Also, voluntary activities (OR = 0.823, 95% CI = 0.776–0.872, P < 0.001) and participation in the associations activities (OR = 0.665, 95% CI = 0.582–0.759, P < 0.001) were negatively associated with physical inactivity. Conclusion. The prevalence of food insecurity and physical inactivity is relatively high among Tehran residents. As a factor affecting the physical activity and food security, social capital can be targeted in interventions to improve physical activity and food security among Iranians.